Single-cell analysis of microglial activation after traumatic brain injury reveals immune signaling pathways linked to mitochondrial dysfunction and brain aging - Sun, Ming; Wu, Chao; Wu, Jingjing; Liu, Lixin; Gu, Liang; Wang, Zihao; Yang, Xue; Xu, Feng (Frontiers in Aging Neuroscience, 2026)
ObjectiveMicroglia are the primary immune cells in the central nervous system (CNS); however, their temporal and spatial responses to traumatic brain injury (TBI) at the single-cell level remain poorly defined. This study aimed to map the dynamic microglial responses to TBI using single-cell transcriptomics and validate key signaling pathways in vitro.MethodsA single-cell transcriptomic atlas was reconstructed from publicly available datasets comprising cortical, hippocampal, and blood samples from 35 mice (11 blood, 12 cortex, and 12 hippocampus) subjected to TBI or sham treatment at 24 h and after 7 days. Comparative analyses were conducted to investigate the heterogeneity of myeloid cells, including monocytes, macrophages, and microglia, with a particular focus on activated microglia. The key findings were further validated using quantitative PCR (qPCR) in an in vitro TBI-mimicking model, employing lipopolysaccharide (LPS)-stimulated microglial cell lines to assess changes in gene expression.ResultsTBI induced rapid immune remodeling, including an increase in activated microglia in the cortex, enriched in leukocyte differentiation pathways, and elevated macrophage populations in the cortex and hippocampus, enriched in chemotaxis functions at 24 h. Ligand–receptor (LR) analysis revealed three major signaling axes—Ccl2/Ccl7–Ccr2, Tnf–Tnfrsf1b, and Grn–Flna—associated with monocyte recruitment, M1 polarization, and macrophage differentiation. Validation using qPCR confirmed significant upregulation of Ccl2, Tnf, and Grn in LPS-stimulated microglia, which is consistent with single-cell findings.ConclusionThis study provides the first integrative single-cell transcriptomic map of microglial–myeloid interactions after TBI across multiple tissues and time points, linking microglial signaling to mitochondrial dysfunction and neuroinflammation. These findings lay the foundation for therapeutic strategies targeting myeloid-driven immune regulation in TBI.